Handbook of Global Oral History - Cave, Mark; Leydesdorff, Selma (Handbooks of Literary and Cultural Studies, 2026)
The Handbook of Global Oral History inspires the reader to be more open in their conception of what oral history is and how it is applied within a variety of disciplines to unlock meaning in human experience. The book brings together scholars from around the world in the areas ranging from memory studies, Indigenous history and journalism to anthropology, trauma, and archival studies. Their essays provide fresh theoretical insights to the field of oral history, and broaden current notions of how oral history fieldwork can be applied and how archived interviews can be interpreted. Contributors: Nēpia Mahuika, John Waiko, David Carey, Jan Jansen, Dr. Sumallya Mukhopadhyay, Pothiti Hantzaroula, Dr. Nompilo C. Ndlovu, Nadia Jones-Gailani, Denise Phillips, Verena Lucia Nägel, Alexander Prenninger, Alejandro Castillejo-Cuéllar, Vannessa Hearman, Nanci Adler, Alexander Freund, Sofia Bach, Claudia Dueck, Jeff Sahadeo, Mark Cave, Anahi Naranjo Jara, Kate Darian-Smith, Carla Pascoe Leahy, Dr Deb Anderson, Dr Nicolette Snowden, Pilar Riaño-Alcalá, Jeff Friedman, Naomi Frost, Steven High, Dr. Tomoyo Nakao, Selma Leydesdorff, Dori Laub, Yasmin Saikia, Stephen M. Sloan, Melissa M. Sloan, Sean Field.